Validity and Reliability of a Novel Integrative Motor Performance Testing Course for Seniors: The “Agility Challenge for the Elderly (ACE)” - Lichtenstein, Eric; Faude, Oliver; Zubler, Aline; Roth, Ralf; Zahner, Lukas; Rössler, Roland; Hinrichs, Timo; van Dieën, Jaap H.; Donath, Lars (Frontiers in Physiology, 2019)
Background: Assessing traditional neuromuscular fall risk factors (i.e. balance, gait, strength) in the elderly has so far mainly been done independently. Functional and integrative testing approaches are scarce. The present study proposes an agility course for an integrative assessment of neuromuscular and also cardiocirculatory capacity in seniors - and tests its criterion validity and reliability. Methods: Thirty-six seniors (age: 69.0 ± 2.8 y; BMI: 25.4 ± 3.5 kg/m2; sex: 19 males/17 females; weekly physical activity: 9.4 ± 5.5 h) participated. They completed four trials of the ACE-course in two sessions separated by 1 week. The course consists of three segments focusing on different agility aspects. Cardiovascular capacity was assessed by six-minute walk test (6MWT), neuromuscular capacity by static, dynamic and perturbed standing balance tasks, habitual gait speed assessment and rate of torque development testing. Parameters’ predictive strength for the ACE performance was assessed by regression analysis. Reliability was calculated with intraclass correlation coefficients and coefficients of variation. Results: Men completed the course in 43.0 ± 5.7 s and women in 51.9 ± 4.0 s. Overall and split times were explained by 6MWT time (ηp²=0.38-0.44), gait speed (ηp²=0.29-0.43) and to a lesser extent trunk rotation explosive strength (ηp²=0.05-0.12). Static and dynamic balance as well as plantar flexion strength explained the performance in some segments to a very small extent (ηp²=0.06-0.08). Good between- and within-day reliability were observed for total course and split times: The ICC for the between-day comparison was 0.93 [0.88-0.96] and ranged between 0.84 and 0.94 for split times. The within-day ICC was 0.94 [0.91-0.97] for overall time and 0.92 – 0.97 for split times. Coefficients of variation were smaller than 5.7% for within and between day analyses. Conclusion: The ACE course reflects cardiocirculatory and neuromuscular capacity, with the three ACE segments potentially reflecting slightly different domains of neuromuscular (static and dynamic balance, ankle and trunk strength) performance, whereas cardiocirculatory fitness and gait speed contribute to all segments. Our test can detect changes in overall performance greater than 5.7% and can thus be useful for documenting changes due to interventions in seniors.